Al2O3 pellet supported transition metal oxide catalysts for H2 generation from alkaline NaBH4 solution - Salt, Selin; Celep, Kevser; Figen, Halit Eren; Elibol, Meltem Karaismailoglu (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Hydrogen production from the hydrolysis of sodium borohydride (NaBH4) offers a safe, controllable approach to on-demand fuel generation. However, its slow kinetics require efficient catalysts. In this study, cobalt-, copper-, and vanadium-oxide catalysts supported on Al2O3 pellets were synthesized using wash-coating and electroless deposition methods. Their physicochemical properties were investigated. Results reveal that electroless deposited catalysts consistently outperformed wash-coated ones. Among them, the catalyst with the nominal structure of Co3O4/CuV2O6/Al2O3 exhibits the highest activity, with hydrogen generation rates rising from 3.5 to 7.7 mL/ min, corresponding to an average rate of 7.5 mL/min under extended testing conditions. This performance is credited to the synergistic interaction of Co and Cu species. Notably, the superior activity of the electroless deposited catalyst was achieved despite its lower overall metal loading, highlighting the critical role of dispersion and metal-support interactions. The enhanced performance of electroless deposited catalysts is therefore linked to the formation of multiple active phases, as revealed by structural analysis. These results highlight the importance of synthesis strategy and elemental synergy in advancing transition-metal-based catalysts for efficient hydrogen generation from alkaline NaBH4 solutions.
Keywords: Catalyst; Sodium borohydride; Hydrogen generation; Wash coating; Electroless deposition; SODIUM-BOROHYDRIDE; HYDROLYSIS; RAMAN; NI; COPPER; CU; Chemistry; Electrochemistry; Energy & Fuels